Ledstilling i ledsætninger i dansk som arvesprog i Argentina. Et foreløbigt studium - Hartling, Anna Sofie (Ny forskning i grammatik, 2016)
This paper presents a case study of word order variation in subordinate clauses (henceforth ‘subclauses’) in Heritage Danish in Argentina. In European Danish, the placement of the sentence adverbial traditionally distinguishes so-called main clause word order (conj>S>Vfin>Adv) and subclause word order (conj>S>Adv>Vfin). The paper shows that this normative distinction still holds in more than half of the subclauses in Heritage Danish in Argentina, and, except for the relative clauses, to an even higher degree than in colloquial European Danish. Hence, the word order distribution in Heritage Danish also differs from Heritage Norwegian and Swedish where word order in subclauses has become optional due to incomplete acquisition of the heritage language.